Friends or foes? Interactions between Indonesia's international investment agreements and national investment law - Axel Berger; Jan Knörich (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
Developing countries regularly conclude international investment agreements with the objective of attracting foreign investment. Such agreements form commitments to far-reaching international rules on investment issues, and usually allow foreign investors to sue countries for compensation in cases of non-compliance with treaty provisions. This study argues that such non-compliance is a result of inconsistencies between national investment laws and measures and international treaty commitments. Through an in-depth empirical examination of Indonesia's investment law, the study analyses the complexities of managing this interaction between national investment law and international investment agreements, and identifies appropriate strategies and governance mechanisms to enhance coherence between these two areas. The implications for national policy space and economic development are considered throughout.
Keywords: 330; Handel und Investitionen